2022
DOI: 10.18502/jimc.v4i4.8468
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Health Care Workers at Imam Khomeini Hospital in Tehran During COVID-19 Pandemic

Abstract: Background: In this study, screening of mental health problems among Health Care Workers (HCWs) was performed in order to assess the prevalence and severity of depression, anxiety, and perceived stress at Iran’s largest teaching hospital during the COVID-19 pandemic. Methods: In this cross-sectional study, HCWs who were working professionally in specific wards for COVID-19 patients were selected by availability sampling. The patients who met the inclusion criteria and answered the submitted questions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Reducing work hours and limiting clinical services to emergency procedures can be useful advice for only a limited time, as they may result in financial problems 14,39 . Therefore, it seems that measures such as increasing the general vaccination rate, improving the identification system of patients infected with COVID‐19, providing enough PPE, identifying HCWs at risk of developing psychiatric disorders, appreciating HCWs' efforts during the pandemic era, and providing available psychiatric and psychological services for them can be more effective and efficient 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing work hours and limiting clinical services to emergency procedures can be useful advice for only a limited time, as they may result in financial problems 14,39 . Therefore, it seems that measures such as increasing the general vaccination rate, improving the identification system of patients infected with COVID‐19, providing enough PPE, identifying HCWs at risk of developing psychiatric disorders, appreciating HCWs' efforts during the pandemic era, and providing available psychiatric and psychological services for them can be more effective and efficient 40 …”
Section: Discussionmentioning
confidence: 99%
“…14,39 Therefore, it seems that measures such as increasing the general vaccination rate, improving the identification system of patients infected with COVID-19, providing enough PPE, identifying HCWs at risk of developing psychiatric disorders, appreciating HCWs' efforts during the pandemic era, and providing available psychiatric and psychological services for them can be more effective and efficient. 40 This study is conducted by a cross-sectional method; therefore, it had some inherent limitations. We did not have any data regarding baseline mental health conditions among dental care providers who participated in the study.…”
Section: Ptsdmentioning
confidence: 99%
“…The prevalence of burnout among healthcare workers in the COVID-19 has also been frequently studied in different regions and countries and high-level burnout rates of 49.3% ( 12 ) and 50% ( 13 ), to more than 60% ( 14 ) and even 67% ( 15 ) have been reported among healthcare workers in the COVID-19 pandemic. Studies have also shown high rates of anxiety and depression among Iranian healthcare workers in the COVID-19 pandemic ( 16 18 ), especially among the female ( 19 ). Iranian studies have shown negative psychological experiences caused by COVID-19 in healthcare workers, such as fatigue, discomfort, and helplessness due to high-intensity work, anxiety, and worry about family members ( 20 ).…”
Section: Introductionmentioning
confidence: 99%